2001
DOI: 10.1074/jbc.m102302200
|View full text |Cite
|
Sign up to set email alerts
|

Two Vicinal Cysteines Confer a Peculiar Redox Regulation to Low Molecular Weight Protein Tyrosine Phosphatase in Response to Platelet-derived Growth Factor Receptor Stimulation

Abstract: Low molecular weight protein tyrosine phosphatase (LMW-PTP) is an enzyme involved in platelet-derived growth factor (PDGF)-induced mitogenesis and cytoskeleton rearrangement because it is able to bind and dephosphorylate the activated receptor. LMW-PTP presents two cysteines in positions 12 and 17, both belonging to the catalytic pocket; this is a unique feature of LMW-PTP among all protein tyrosine phosphatases. Our previous results demonstrated that in vitro LMW-PTP is oxidized by either H 2 O 2 or nitric ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
154
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(164 citation statements)
references
References 40 publications
9
154
1
Order By: Relevance
“…It is worth noticing that in comparison with these other sulfhydryl reductants, NAC is not toxic. Although also protein tyrosine phosphatases should be activated by sulfhydryl reduction, 3 the lack of Y530 dephosphorylation excludes a role of phosphatases in this NAC-mediated c-Src inactivation. More experiments are in progress to better elucidate this mechanism for c-Src inactivation and to quantitatively determine the oxidized/reduced -SH groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noticing that in comparison with these other sulfhydryl reductants, NAC is not toxic. Although also protein tyrosine phosphatases should be activated by sulfhydryl reduction, 3 the lack of Y530 dephosphorylation excludes a role of phosphatases in this NAC-mediated c-Src inactivation. More experiments are in progress to better elucidate this mechanism for c-Src inactivation and to quantitatively determine the oxidized/reduced -SH groups.…”
Section: Discussionmentioning
confidence: 99%
“…1 In particular, protein tyrosine phosphatases play a pivotal role in the control of cell cycle and differentiation, and were reported to be regulated through the redox state of their cysteine -SH residues. 2,3 Also protein tyrosine kinases have an essential role in the control of cell proliferation and differentiation. For three of them, Yes, Fyn and c-Src, a redox regulation has been recently reported 4,5 and particularly for c-Src, it apparently implies a reversible change in the redox state of a group of four cysteine residues close to the catalytic site.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidative reaction of cysteine with H 2 O 2 may change structure and function of protein mediating response to changes of redox state in the cell (61,62). An important protein effector by which H 2 O 2 signaling occurs is the family of PTPs (34,(36)(37)(38)63,64). PTPs constitute a large family of important regulatory enzymes that play a key role in several physiological functions.…”
Section: A Signaling Proteins In Which Critical Cysteines Are Modifiedmentioning
confidence: 99%
“…A change in a single Cys residue is sufficient to have a profound effect on the molecular architecture of PTPases and thus on their enzymatic activity (Mayadas and Wagner, 1992;Chiarugi et al, 2001;Paget and Buttner, 2003;Tonks, 2005;Zimmermann et al, 2007;Winterbourn and Hampton, 2008;Álvarez et al, 2009;Bucciarelli et al, 2009). With this in mind, we searched the protein homology of ZmRIP1 and found that distinct differences between ZmRIP1 and its homologs exist in the Cys residues at two sites (i.e.…”
Section: Discussionmentioning
confidence: 99%